A Visual-based Project Production Package for Design & Technology Subject, Based on Computational Thinking Skills Across-STEM - Ismail, Rahimah; Zaman, Halimah Badioze; Mohammad, Ummul Hanan (Society of Visual Informatics, 2022)
Computational Thinking (CT) is a concept introduced in the problem-solving process and is a systematic way of thinking not only in computer science but also in various other disciplines. Awareness to apply CT into education at different curricular levels has started from the beginning of schooling in various contexts and directions. Development of a Visual-based Project Production Package Model (KHP4) across â€“STEM, using computational thinking skills in the Reservoir Crop System (ST2) project production process for the Design and Technology (RBT) subject in primary schools, Â aims to improve students' problem solving and thinking skills, to be more critical, creative and innovative, which includes the development of RBT learning model and modules. This life cycle model is adapted form the ADDIE modeL, which integrates the concept of 'prototyping' based on five (5) main phases, namely analysis, design, development, implementation, and evaluation. Assessment with aprropriate iteration. This development model is adapted based on the COMEL learning Model with the practice of interactive, fun, interesting and motivating learning for students with the addition of a new component and elements. Thus, this paper highlights the evaluation of the Visual-based Project Production Package Development (KHP4) model in Project Production which is able to improve thinkingand problem solving skills, Â based on CT to prepare students towards 21st century learning and to instill sustainable development practices in students in facing Energy Transition that is experienced nationally and globally.